Pencegahan Stunting Perspektif Pendidikan Islam - artikel4 (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi Pancor, 2025)
Stunting or malnutrition is still an actual problem today. Various efforts have been made to prevent and deal with stunting that continues to spread in Indonesia. This research aims to examine the concept of stunting prevention through an Islamic approach. The research uses a qualitative method by analyzing a series of words in various literature sources and readings so as to produce written data in the form of narratives. In addition, the research is also supported by using a library research system or also known as library research. The research shows that Islamic values such as maintaining health (hifz al-nafs), parental responsibility, clean living principles, and consuming halal and good food can be a strong foundation in stunting prevention efforts. Therefore, it is important for every individual, whether parents, families, or individuals themselves to recognize Islamic education on stunting prevention. It is recommended for community leaders to emphasize Islamic values in the stunting prevention socialization program in the midst of society, in order to give birth to a healthy and spiritually intelligent generation.